2014
DOI: 10.5209/rev_hics.2014.v19.45108
|View full text |Cite
|
Sign up to set email alerts
|

Redes sociales y TIC, su papel en la educación superior del siglo XXI

Abstract: Resumen:El siglo XXI ha supuesto una transformación en el ámbito cultural de las sociedades, fruto del surgimiento de diferentes maneras de generar conocimiento y de transmitir información que ha afectado a todos los ambientes académicos. Los docentes están obligados a formarse en el uso, conceptos y alcances de las redes sociales y las TIC aunque estas no pueden reemplazar las herramientas educativas preexistentes. Todo ello implica un replanteamiento del sistema educativo que permita hablar de una verdadera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Firstly, the need for teachers to be technologically competent seems to be highly relevant to students' academic performance (Seifert, 2016). Following this assumption, Martínez (2014) expresses that educators not only have to be trained in the attitudes towards and implications and possibilities of SNSs, but also in some of their technology skill set, such as creating content, analysing information, evaluating procedures and tools, or disseminating data widely. Considering that students are digital natives, teachers are required to become 'as savvy as their students' (Blair & Serafini, 2014, p. 28), which means that both parties should develop similar digital competencies (Rama & Chiecher, 2012).…”
Section: Teacher-student Performancementioning
confidence: 99%
See 3 more Smart Citations
“…Firstly, the need for teachers to be technologically competent seems to be highly relevant to students' academic performance (Seifert, 2016). Following this assumption, Martínez (2014) expresses that educators not only have to be trained in the attitudes towards and implications and possibilities of SNSs, but also in some of their technology skill set, such as creating content, analysing information, evaluating procedures and tools, or disseminating data widely. Considering that students are digital natives, teachers are required to become 'as savvy as their students' (Blair & Serafini, 2014, p. 28), which means that both parties should develop similar digital competencies (Rama & Chiecher, 2012).…”
Section: Teacher-student Performancementioning
confidence: 99%
“…This may suggest some limitationswhen leading students to develop their total activity exclusively across digital spaces. On the one hand, some limitations are related to the promotion of learners' passive attitudes towards participation, lower commitment of teachers when students use digital environments, or the lack of physical teacher-student' interaction (Alvarez-Flores & Gómez, 2013;Ling, 2014;Martínez, 2014;Norman et al, 2015;Rama & Chiecher, 2012;Túñez & Sixto, 2012). On the other hand, other studies have found a relationship between the frequency in the use of SNSs and academic achievement, so that the latter increases when the student displays a moderate use of SNSs (Abu-Shanab & Al-Tarawneh, 2015;Al-Yafi, El-Masri, & Tsai, 2018;Paul, Baker, & Cochran, 2012) and avoids passive or addictive uses (Arquero & Romero-Frías, 2013;Buck, 2012;Gafni & Deri, 2012;Huang, 2018).…”
Section: Teacher-student Performancementioning
confidence: 99%
See 2 more Smart Citations
“…El deseo de emancipación de la tradición es un fenómeno nuevo con la llegada de la Ilustración y corrió parejo al desprestigio de cualquier forma de autoridad, dando paso al ideal kantiano de la autonomía del individuo (Hildebrand, 2003). Señala Maritain (2006) que parece claro que los argumentos expuestos por Lutero sobre el valor del libre examen y la crítica del papel de la Iglesia en la propia salvación fueron posteriormente desarrollados con vigor por Descartes y Rousseau y sirvieron para articular los principios liberadores y emancipadores que provocaron el advenimiento ilustrado y el pensamiento moderno.…”
Section: La Crisis Histórica De La Autoridad Y Su Necesidad Como Elem...unclassified